Subjective performance evaluations and employee careers - Anders Frederiksen; Fabian Lange; Ben Kriechel (Institute for the Study of Labor (IZA), 2012)
Firms commonly use supervisor ratings to evaluate employees when objective performance measures are unavailable. Supervisor ratings are subjective and data containing supervisor ratings typically stem from individual firm level data sets. For both these reasons, doubts persist on how useful such data are for evaluating theories in personnel economics and whether findings from such data generalize to the labor force at large. In this paper, we examine personnel data from six large companies and establish how subjective ratings, interpreted as ordinal rankings of employees within narrowly defined peer-groups, correlate with objective career outcomes. We find many similarities across firms in how subjective ratings correlate with earnings, base pay, bonuses, promotions, demotions, separations, quits and dismissals and cautiously propose these as empirical regularities.
urn:nbn:de:101:1-201206146489
Keywords: M5; 330; subjective performance ratings; personnel data; employee careers; Personalbeurteilung; Erwerbsverlauf; Großunternehmen; Welt